Design and ergonomic considerations for the filmless environment. - Siddiqui KM; Chia S; Knight N; Siegel EL (Journal of the American College of Radiology, 2006)
Planning and executing the redesign of a traditional institutional radiology reading room to conform to the radically different requirements of digital imaging are reviewed, with examples drawn from the authors' experience and from the growing body of literature on this subject. Included are best-practice recommendations and real-life examples on initial design and planning, stakeholder involvement, identifying and hiring consultants, architectural planning, the designation of a radiology point person, rethinking room and workstation design, the selection of ergonomic furniture and fittings, identifying optimal environmental elements, fine tuning and lessons learned, and going digital.